Stagnation-point flow of Williamson fluid along a stretched plate with convective thermal condition and activation energy - Salawu, Sulyman Olakunle (Zielona Góra: Uniwersytet Zielonogórski)
The implication of a stagnation-point flow together with the influence of activation energy in a Williamson fluid, which consists of tiny particles, over an expansive plate is analyzed numerically. Conditions of convective heat and mass motion with features of irregular movement and thermal-migration of particles influenced by viscous dissipation and convective heat surface condition are checked in the study.
Keywords: activation energy; Williamson fluid; stagnation-point; convective condition